Variation Among Japanese Miso Breweries in Indoor Microbiomes is Mainly Ascribed to Variation in Type of Indoor Surface - Roger T. Koide; Makoto Kanauchi; Yasushi Hashimoto (Current Microbiology, 2024)
Miso is a microbially-fermented soybean food. The miso brewery indoor microbiome contributes to miso fermentation. Japanese breweries are not climate-controlled, so indoor spaces are strongly affected by the prevailing climate. Because climate influences microorganism distribution, our first hypothesis is that latitude, as a proxy for climate, is a major determinant of brewery indoor microbiome structure. Breweries vary in interior surface materials and in the way operations (steaming, processing, fermenting) are apportioned among rooms. Therefore, our second hypothesis is that more variability in indoor microbiomes exists among breweries than can be ascribed to a latitudinal gradient. Most miso produced today is inoculated with commercial microbial strains to standardize fermentation. If commercial strains outcompete indigenous microbes for membership in the indoor microbiome, this practice may homogenize indoor microbiomes among regions or breweries. Therefore, our third hypothesis is that inoculant fungal species dominate indoor fungal communities and make it impossible to distinguish communities among breweries or across their latitudinal gradient. We tested these hypotheses by sampling indoor surfaces in several breweries across a latitudinal gradient in Japan. We found that latitude had a significant but relatively small impact on indoor fungal and bacterial communities, that the effect of brewery was large relative to latitude, and that inoculant fungi made such small contributions to the indoor microbiome that distinctions among breweries and along the latitudinal gradient remained apparent. Recently, the Japanese Ministry of Agriculture, Forestry and Fisheries specified fungal inoculants to standardize miso production. However, this may not be possible so long as the indoor microbiome remains uncontrolled.